Hubungan Inisiasi Menyusui Dini Dengan Kelancaran Pengeluaran Asi Pada Ibu Post Partum Di Puskesmas Kota Datar Kecamatan Hamparan Perak Kabupaten Deli Serdang Tahun 2023 - Suriana Suriana; Nopalina Suyanti Damanik; Martaulina Sinaga; Adelina Sembiring (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Considering how important Early Breastfeeding Initiation is, especially in Indonesia, it is being implemented, one of the main goals of which is to ensure smooth breastfeeding, where the aim of the baby getting breast milk is to be able to develop the baby's maximum potential (Rahmat, 2018). This study aims to analyze the relationship between early initiation and the smooth production of breast milk in post-partum mothers at the Datar City Health Center, Hamparan Perak District, Deli Serdang Regency in 2023. This research is an analytical description with a cross-sectional approach and bivariate data analysis is the data analysis used in the research to determine the relationship or influence of the independent variable with the dependent variable using chi-square test analysis, at the p-value statistical significance limit α (0.05), then Ha: accepted and Ho: rejected (Hardani, 2020).Based on the table above, it can be explained that of the 32 respondents, those who did not initiate early breastfeeding, the majority of mothers' breast milk was not flowing smoothly, 13 (41%). Based on this table, it can be seen that there is a relationship between early initiation and the smooth production of breast milk for post-partum mothers at the Kota Datar Community Health Center, Hamparan Perak District, Deli Serdang Regency in 2023 with a p value of 0.001.This means that there is a relationship between early initiation and the smooth production of breast milk for post-partum mothers at the Datar City Health Center, Hamparan Perak District, Deli Serdang Regency in 2023